Keanekaragaman Burung di Desa Karangasem Kecamatan Wirosari Kabupaten Grobogan Jawa Tengah - Margareta Rahayuningsih; Fajar Adi Purnomo; Bambang Priyono (Biosaintifika: Journal of Biology & Biology Education, 2010)
The aim of this study was to measure the bird’s diversity at Karangasem Village, Wirosari District, Grobogan Regency mainly at the forest habitat, farm land and it settlements. The study was conducted on September until November 2008 used point count method. The data of birds species and its number analyzed by Shanon-Wiener species diversity index (H’), evenness index (E), dominance index (Di) and similarity index of Jaccardto describe the similar species of birds inter-habitat at Karangasem. The result indicated that there are 43 birds species of 22 families recorded at the location. About eight species among them are protected by the government, two among them included into CITES appendix II and one of them included into Vulnerable category of IUCN Red List. The birds diversity index and evenness index in the village of Karangasem ranges from 1.9 to 2.7 and 0.68 to 0.8. The highest and most dominant species are Collocalia linchi, Pycnonotus aurigaster, Lonchura leucogastroides and Lonchura punctulata. The analysis of Jaccard’s similarity index showed that the forests had more similarity to settlements than rice farming, which means there are high differences between habitats. There are differences in composition, structure, and featured bird species of the habitat, whichcaused low similarity index between the habitat ranges from 19.23% to 25.71%. Keywords: Birds diversity, point count, Karangasem